The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/cge.13384
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide compound heterozygosity analysis highlighted 4 novel susceptibility loci for congenital heart disease in Chinese population

Abstract: Genome-wide association studies (GWASs) have achieved great success in deciphering the genetic cause of congenital heart disease (CHD). However, the heritability of CHD remains to be clarified, and numerous genetic factors responsible for occurrence of CHD are yet unclear. In this study, we performed a genome-wide search for relaxed forms of compound heterozygosity (CH) in association with CHD using our existing GWAS data including 2265 individuals (957 CHD cases and 1308 controls). CollapsABEL was used to ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Genomic wide association studies (GWAS) involve the comparison of genetic variants of different affected individuals within the society and whether the variants are associated with a certain trait. GWAS, therefore, can be used to detect multiple genetic risk factors which contribute to congenital heart diseases [59]. CHDs being heterogeneous group of diseases, the use GWAS may give us an insight to the etiology of CHDs [60].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic wide association studies (GWAS) involve the comparison of genetic variants of different affected individuals within the society and whether the variants are associated with a certain trait. GWAS, therefore, can be used to detect multiple genetic risk factors which contribute to congenital heart diseases [59]. CHDs being heterogeneous group of diseases, the use GWAS may give us an insight to the etiology of CHDs [60].…”
Section: Introductionmentioning
confidence: 99%
“…A GWAS in the Han Chinese population identified two loci, 1p12 and 4q13.1, associated with CHD. Another study in the Han Chinese using a compound heterozygous model identified four additional loci that explained 7.8% of the CHD variance in the population, suggesting that multiple modes of inheritance are contributing (Jiang et al 2018). Several studies have examined specific groups of CHD including left-sided lesions and TOF and have identified susceptibility loci that account for a small proportion of the genetic variation in each case (Cordell et al 2013b;Mitchell et al 2015;Hanchard et al 2016).…”
Section: Common Variants and Chdmentioning
confidence: 99%
“…In addition to the traditional GWAS of inherited variants (summarized above and in Table ), several additional GWAS of CHDs have been conducted. These include a study of inherited compound heterozygous genotypes (Jiang et al, ), and a study of inherited genotypes and neurodevelopmental outcomes following cardiac surgery in infancy (Kim et al, ). In addition, three GWAS have focused on the maternal genotype (Agopian et al, ; Agopian et al, ; Mitchell et al, ).…”
Section: Gwas Of Selected Birth Defectsmentioning
confidence: 99%